The role of septal surgery in cosmetic rhinoplasty - PARRILLA, C. (Pacini Editore SpA, 2013)
Septoplasty is performed to resolve breathing problems, but it often becomes pivotal to correct external nasal deviation, representing a central step in rhinoplasty surgery. Even in patients with no functional problems, septal surgery may represent the best solution for obtaining a proper realignment of the external nasal pyramid. One-stage septorhinoplasty has become the standard of treatment for a deviated nose, hence septoplasty cannot be considered as a separate procedure to perform before or after rhinoplasty or as a partial operation subject to later revision. The aim of this article is to discuss the close relationship between the nasal septum and the aesthetics of the nose, and how a graduated surgical approach for the correction of septal deviations could affect the external deviated nose.